Analisis motivasi belajar matematika siswa melalui media google meet terhadap kemampuan pemahaman konsep matematis siswa di masa pandemi COVID-19 - Islami Nur, Fadillah; Kusumo, Sri Wibowo (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
Purpose: This study evaluates the correlation between learning motivation, self-regulation, and the use of Google Meet in enhancing students' mathematical concept understanding of systems of linear equations (SPLDV).Design/methodology/approach: A quantitative correlational design was employed with 32 students at SMPN 4 Tambun Selatan. Data were collected via the Mathematics Attitudes and Perceptions Survey (MAPS), self-regulation inventories, and concept mastery tests, then analyzed using Bayesian estimation and regression.Findings: Findings reveal a significant positive correlation (r = 0.78) between motivation and concept mastery. Motivation and self-regulation contribute 61% to learning outcomes, while synchronous interaction via Google Meet effectively mitigates mathematics anxiety and fosters creative thinking.Practical implications: Educators should integrate synchronous feedback and independent study workbooks to optimize spaced retrieval practice, ensuring long-term knowledge retention in digital environments.Originality/value: This research contributes to the literature by synthesizing psychological dispositions with synchronous technology, validating the